2002
DOI: 10.1046/j.1464-410x.2002.02812.x
|View full text |Cite
|
Sign up to set email alerts
|

High initial efficacy of full‐spectrum therapy for nocturnal enuresis in children and adolescents

Abstract: Objective To investigate the initial efficacy and predictive factors of full-spectrum therapy in the treatment of children and young adolescents with nocturnal enuresis (NE). Patients and methods Combined therapy for NE comprises an enuresis alarm, bladder training, motivational therapy and pelvic floor muscle training, and is more effective than each of the components alone or than medical intervention. A total of 60 children and adolescents (aged 4-20 years) with NE were treated once a week with full-spectru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 22 publications
0
6
0
3
Order By: Relevance
“…It has been suggested that in children with NE the short‐term results of full‐spectrum therapy, combining an enuresis alarm, bladder training and motivational therapy, is 76–87%, and thus better than each treatment alone and better than medication or psychological treatment [17,18]. However, the present data show that a stepwise approach also results in a fairly high short‐term cure rate of 67%, and even prolonged RCT as sole treatment seems successful, even in children with refractory NE who are more difficult to treat.…”
Section: Discussionmentioning
confidence: 53%
“…It has been suggested that in children with NE the short‐term results of full‐spectrum therapy, combining an enuresis alarm, bladder training and motivational therapy, is 76–87%, and thus better than each treatment alone and better than medication or psychological treatment [17,18]. However, the present data show that a stepwise approach also results in a fairly high short‐term cure rate of 67%, and even prolonged RCT as sole treatment seems successful, even in children with refractory NE who are more difficult to treat.…”
Section: Discussionmentioning
confidence: 53%
“…Alarm and reward system are the components of arousal therapy/training, which was reported to have a high efficacy and low relapse rate in an early literature [24]. However, they have not been recommended by the guideline [10] because there is not enough clinical evidence, which is similar to FSHT [25].…”
Section: Complex Behavioral Interventionsmentioning
confidence: 99%
“…[ 34 ] Combination therapy with an enuresis alarm, bladder training, motivational therapy, and pelvic floor muscle training was successful in 87% of patients after 14 weeks and improved functional bladder capacity from 53% to 88%. [ 35 ]…”
Section: Treatment Of Primary Nocturnal Enuresismentioning
confidence: 99%